기초자치단체의 다문화가족지원 조례 제정현황과 내용에 관한 분석: 경기도 내 시, 군을 중심으로 - 오세민; 박정훈; 홍성휘 (다문화와 평화, 2014)
본 연구는 다문화의 배경을 가진 주민의 양적증가와 같은 시대적 특성과 사회복지서비스의 대상자로 분류되는 다문화가족 관련 조례가 경기도 내 기초자치단체에 무엇이 있으며, 내용의 공통점 혹은 차이점에 대하여 탐색하여 문제점을 도출하고, 이를 근거로 다문화가족 지원에 대한 조례의 한계점을 밝힘과 더불어 개선방안에 대해 모색하고자 하였다. 이러한 연구목적을 달성하기 위해 경기도 내 기초자치단체의 조례를 세분화하기 위하여 상위법인 다문화가족지원법의 지원내용을 검토, 조례를 분석하였다. 이에 대한 주요결과는 다음과 같다. 첫째, 경기도 내 31개 기초자치단체 중, 총 25개의 기초자치단체에서 다문화가족 지원에 대한 조례를 제정하고 있으며, 특히, 13개 기초자치단체의 경우, 외국인주민(유학생, 외국인근로자, 재외동포 등)을 정책의 대상에 포함하여 복지 사각지대를 최소화하기 위한 기초근거를 마련하고 있는 것으로 나타났다. 둘째, 기초자치단체장의 책무가 미흡한 것으로 나타났다. 대체적으로 시책수립에 대한 조항은 마련되어 있으나, 이외에 주민의 정책(행정) 참여유도나 시책을 전담으로 추진하여야 하는 부서설치, 다문화 사회에 대한 제반 여건을 조성하는 차원의 체계는 부족한 것으로 나타났다. 셋째, 각종 위원회가 옥상옥이 될 우려가 있는 것으로 나타났다. 일부 지역의 조례에서 규정하고 있는 위원회 혹은 협의체 등의 경우, 그 성격이 뚜렷하지 못함은 물론, 심의나 평가에 대한 기능보다는 자문의 기능이 강한 것으로 나타났다. 넷째, 정책을 실현하는 서비스 공급 체계 기반에 관한 조항의 미흡함으로 이들의 서비스 개발 및 제공의 안정성 및 연속성을 담보하기에는 한계가 있다. 이러한 문제의식을 바탕으로 기초자치단체에서 수립하고 있는 조례의 체계 방향성 및 발전방안을 다음과 같이 제언하였다. 첫째, 국적 미취득자(유학생 및 외국인근로자)의 복지 증진에 대한 기초자치단체의 책임성이 강화되어야 한다. 둘째, 정책의 실효성을 고려하여 정책평가 기능이 보완되어야 한다. 이와 더불어 시책의 객관적인 평가가 용이할 수 있도록 기초자치단체장의 책무를 세분화하여 이에 대한 평가도 함께 이루어져야 할 것이다. 셋째, 조례에서 제시하고 있는 위원회와 협의체의 기능을 적절히 설정하여야 한다. 위원회의 경우, 정책에 대한 심의와 평가의 기능을 중심으로 운영을 하며, 협의체의 경우, 다양한 서비스 공급기관 간에 네트워크로써 서비스 공급하는 협의기구로 기능을 설정하는 것이 바람직할 것이다. 넷째, 다문화 정책을 일선 현장에서 구현하는 서비스 공급 주체에 대한 조항의 개정이 요구된다. 따라서, 서비스 공급 체계의 안정성 및 서비스 제공의 연속성 등을 담보할 수 있는 방안으로써, 설치 근거를 강제조항으로 개정하여야 할 것이다. The purpose of this study is to find out the characteristics of the times such as quantitative increase of residents with multicultural background and ordinances of primary local governments in Gyeonggido with respect to multicultural families classified into subjects of social welfare services and explore similarities or differences of the contents to derive problems and seek improvement plans of ordinances for Multicultural Family Support based on them. In order to achieve this research objective, we reviewed the support contents of Multicultural Family Support Act, the upper level law and analyzed ordinances to subdivide ordinances of primary local governments in Gyeonggido.The main results are as follows. First, of 31 primary local governments in Gyeonggido, a total of 25 primary local governments enacted ordinances for multicultural family support and especially, 13 primary local governments turned out to include foreign residents (international students, foreign workers, overseas Koreans etc.) in the target of the policy to prepare for the foundation to minimize welfare blind spot. Second, the duty of the head of the primary local government turned out to be insufficient. Generally, provisions for policy establishment have been prepared but the establishment of the division that should take full charge of inducing residents` participation in policy (administration) or policy and the system for various conditions for multicultural society were found not to be enough. Third, it turned out that various committees may be unnecessary. In case of committee or council etc. prescribed in the ordinances of some areas, it turned out that not only the nature is not apparent but the function of advice is strong rather than function of consideration or evaluation. Fourth, due to the inadequate provisions about service delivery system base realizing policy, there are limitations to guarantee the stability and continuity of development and delivery of these services. Based on these critical minds, we suggested system directivity and development plan of ordinances enacted by primary local governments as follows. First, sccountability of primary local governments should be strengthened for welfare promotion of those who did not acquire citizenship (international students, foreign workers). Second, policy evaluation function should be supplemented by considering the effectiveness of policy. In addition, the duties of the heads of primary local governments should be segmented to facilitate objective evaluation of policies and evaluation on them should be also made. Third, the functions of committee and council presented in the ordinance should be set properly. In case of committee, it will be desirable to operate around the functions of review and evaluation about policy and in case of council, it will be desirable to set the function as the consultation organization of supplying services as the network among various service delivery organizations Fourth, the provision on service supply subjects implementing multicultural policies in the field needs to be amended. Therefore, as the way to guarantee the stability of the service delivery system and continuity of service provision, the installation base should be amended to the mandatory provision.